Household debt and crises of confidence - Thomas Hintermaier; Winfried Koeniger (Quantitative Economics, 2018)
This paper develops a notion of consumer confidence within a dynamic competitive equilibrium framework. In any situation where multiple equilibrium prices on next-period spot markets are equally supported by the state of the economy, confidence is encoded in the subjective probabilities consumers attach to these multiple future outcomes. Our approach characterizes the set of all equilibrium-consistent subjective probabilities, and thereby endogenizes the extent of uncertainty faced by consumers. We use the structure of an economy with collateralized household debt and housing markets to develop and illustrate this concept. Our approach determines the specific range of debt levels at which this economy is vulnerable to crises of confidence, as well as the debt-level-specific extent of confidence-driven house price fluctuations.
Keywords: D84; E32; E44; G01; 330; Consumer confidence; asset price expectations; household debt; collateral constraints